China in der Geschichte der Globalisierung; China's role in the history of globalization - Reinhard Spree (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2015)
– In my view, globalization is a process that has taken place episodically since approximately the beginning of the 16th century. Previously, there were a number of attemps at globalization, which however failed to attain the precondition of regular commercial and communicative relationships among the parts of the globe; nor did they lead to the kind of stable multilateral interdependence that later took place (Osterhamme/Petersson). In chronologically sequenced chapters, I briefly present the driving forces and the consequences of globalization. In the respective chapters, Chinas highly variegated role is explored: from the first attempt at globalization in the 14/15 centuries, which was of an expansive nature; in the first push at globalization from 1500, China was increasingly in retreat; during the surge of globalization in the 19th century, China was an almost insignificant push-toy of the European powers; and in the current situation China may be characterized as a tardive beginner, yet then advancing to a leadership role. In concluding I undertake a framework for understanding the so-called "Chinese Economic Miracle", for which the German term Wirtschaftswunder may readily be substituted. The highly differential significance of China for these various phases of globalization is an arresting example for my hypothesis that globalization may not unreasonably be regarded as a market-driven and invariably politically-fashioned process.
urn:nbn:de:bvb:19-epub-25265-6
Keywords: E65; F60; F63; F69; N4; 330; China; History; Globalization; Macroeconomic Policy; Policy Making; Development; Integration; Public Economics; Slavery; Industrial Revolution; Divergence; Catching Up; Transformation